Visual arts education provisions for primary schools in Turkey - ZUDOVAS, MÜNEVVER MELTEM (Taylor and Francis Inc., 2019)
This article examines the history of art education in Turkey. Since the beginning, the purposes of the arts and art education have been a point of discussion by various authorities. Whether art education should be taught, and how it needs to be taught, have been at the forefront of educationalists' minds. As a result, introducing certain models of art education has been a challenge. The objective of this article is to present the changes in art education since the 19th century in Turkey. The main focus is on art education practices and policies and an overview of key events in Turkey's history of art education. The article also presents issues related to the importance of visual arts education in Turkish primary school settings. In so doing, this research aims to show readers how past developments helped to create the current visual art education policy in Turkey. © 2017, © 2017 Taylor & Francis Group, LLC.
Keywords: Primary school; Turkey; visual arts education